MiR-646 inhibited cell proliferation and migration by targeting P62 in glioma - Fangyu Ye; Heng Zhang; Qianqian Chen; Yanping Gui; Geng Tian; Yuting Ye; Xin Chen; Haijuan Dong; Xiangshan Fan; Jun Chen; RuiYing Yuan; Li Zhao; et al. (Cell Adhesion & Migration, 2025)
MiR-646, a small non-coding RNA, poorly expressed in a variety of tumors. This study aimed to clarify the role of miR-646 and its underlying mechanisms in glioblastoma (GBM). In our study, we found that miR-646 mRNA levels were lower in tumor tissues than in non-cancer tissues. The ability of glioma cells to proliferate, invade, and migrate is diminished by miR-646 overexpression in vitro and in vivo. Mechanistically, miR-646 targeted sequestosome 1 (p62) in the 3’UTR and affected the Keap1/Nrf2 pathway, thus attenuating the expression of the HO-1 gene. In conclusion, this study provided a novel finding that miR-646 tampered with gliomagenesis by regulating the p62/Keap1/Nrf2 axis, which provides a potential target for GBM therapy.